Immunoregulation of chickens’ B lymphocytes and three-dimensional lymphoid tissue culture infected with Newcastle disease virus and infectious bursal disease virus - Teo, Kristeen Ye Wen (2014)
Among the common poultry disease worldwide, Newcastle Disease (ND) and Infectious Bursal Disease (IBD) are contagious and pose a major threat in devastating the poultry industry. Numerous studies were carried out to evaluate host response of avian lymphocytes against Newcastle Disease Virus (NDV) and Infectious Bursal Disease Virus (IBDV) infection, but none has reported on the effect of these highly pathogenic viruses on pure B cells population. As B cell lineage lymphocytes are responsible for the production of antibodies, which play a role in preventing viral infection, this study investigated the responses of enriched B lymphocytes following infection of highly pathogenic NDV and very virulent IBDV strains. Cell viability and proliferation rate of in-vitro cultured B lymphocytes were assessed upon NDV and IBDV infection and results showed that other than the virus infection dosage, time course infection of the virus also affected the viability and inhibited the proliferation of B lymphocytes population in the culture. In the in-vivo study, chickens’ spleen and bursa of Fabricius were investigated on their cell population changes and oxidative stress in relationship with the B lymphocytes response towards the infection of different genotypes of NDV and IBDV. NDV caused increment of macrophage in the organ which led to the elevation of nitric oxide content and NDV genotype VIII induced greater chronic impairment in chickens’ spleen and bursa B cells with lower viral load detected compared to the infection by NDV Genotype VII. In-vivo study with IBDV infection revealed that the virus caused more severe damage in chicken bursa of Fabricius compared to the spleen. Further details showed that the depletion of B lymphocytes in chicken spleen is more relevant to the oxidative stress caused by the virus infection rather than the amount of virus residue in the cells. Meanwhile, the cell death event in B lymphocytes from bursa was in an increasing manner considerably with time of infection and viral load detected in the cells. The second part of the study demonstrated the establishment of an in-vitro culture of chicken lymphoid tissue, simulating chicken embryonic bursa of Fabricius to study the interaction of chicken embryonic B cells upon infection with NDV and IBDV. Following infection with the viruses, cell population changes, viability, apoptosis and viral load were investigated. Results showed that IBDV caused drastic depletion in the matured (IgM+) and immature B cell (Bu-1a) populations while NDV infection induced the production of IgM+ cells, maybe as an effort to combat the virus infection. Cell death by apoptosis was assayed and the result showed that the in-vitro culture of chicken lymphoid tissue is susceptible to NDV and IBDV infection as higher titer of virus infection caused higher frequency of apoptosis as well as higher amount of viral load detected in the culture. The findings showed that the in-vitro model of chicken lymphoid tissue can be used to study the virus and host cells interaction. Moreover, the phenotypic and cell viability changes in the established mini organ upon virus infection are similar to previous reports by other researchers in their in-vitro and invivo approaches. In conclusion, B lymphocytes from chicken spleen and bursa of Fabricius at different age reacted unalike when infected with different strains of pathogenic NDV and IBDV. The depletion of the B lymphocytes population may be caused by population changes, oxidative stress or amount of virus resides in the cells.